Detrimental effects of sand ingression in jet engine ceramic coatings captured with Raman-based 3D rendering. Issue 2 (February 2021) - Barrett, C.; Stein, Z.; Hernandez, J.; Naraparaju, R.; Schulz, U.; Tetard, L.; Raghavan, S.
Abstract: The infiltration of molten calcium, magnesium, and alumino-silicates (CMAS) into jet engine thermal barrier coatings (TBCs) causes an increased stiffness and a destructive phase destabilization eventually leading to thermomechanical failure. Using 3D confocal Raman spectroscopy, the extent of thermochemical degradation was identified by mapping the monoclinic phase volume fraction (mPVF) throughout a standard EB-PVD 7YSZ TBC coating. The mPVF is characterized as a function of depth and infiltration time with microscale resolution. Results show that phase destabilization was most intense along the column's perimeter whereas the core of the column retained most of its original phase. The greatest amount of phase destabilization occurs within the first hour of the interaction after which the average minimum mPVF is 32 %. This value increases to 42 % after a ten-fold increase in interaction time. This ability to quantitatively and non-destructively characterize degradation of CMAS infiltrated TBCs will accelerate development of degradation resistant coatings.